Understanding what impacts on disclosing anal incontinence for women when comparing bowel-screening tools: a phenomenological study - Julie Tucker; Elizabeth Mary Ann Murphy; Mary Steen; Vicki L. Clifton (BMC, 2019)
Abstract Background There is limited research defining the true prevalence of anal incontinence (AI) in women of childbearing age. Understanding the limitations of the current assessment tools in the identification of AI is paramount for identifying the prevalence of AI and improving the care and management for women of childbearing age. The aim of this research was to explore and develop an understanding of women's experiences in disclosing AI when completing a new bowel-screening questionnaire when compared to two established AI tools. Methods A phenomenological qualitative research study was undertaken in a maternity setting in a large tertiary hospital. Parous women in the first trimester of a subsequent pregnancy were recruited to complete a specifically designed screening tool (BSQ), St Marks Faecal incontinence score (Vaizey) and Cleveland (Wexner) score. Qualitative semi-structured interviews were utilised to identify experiences in disclosing AI. Results Women (n = 16, 22-42 years) with a history of anal incontinence either following the first birth (n = 12) or the second (n = 4) provided differing responses between the three assessment tools. All women answered the BSQ while the Vaizey and Wexner scores were more difficult to complete due to clinical language and participants level of comprehension. Women identified three major themes that were barriers for disclosing incontinence, which included social expectations, trusted space and confusion. Conclusion There are barriers for disclosing AI in the pregnant and post-natal population, which can be improved with the use of an easy assessment tool. The BSQ may facilitate discussion on AI between the patient and health professional leading to earlier identification and improvement in short and long-term health outcomes.